Prevalence of attention deficit hyperactivity disorder in schoolchildren in a marginal-urban area of Lima - Livia Segovia, José (2017)
A sample of 212 students was taken of the marginal-urban area of San Martin de Porres district, located in Lima, aged between 6 and 11 years, who were attending a state primary school. A checklist was applied, (validated by the authors) made up by l8 items under DSM IV criteria. The results indicated a prevalence of 16.5 % (IC 95 %=10.7 %-22.3 %), the most predominant type was combined, in boys and the age group of 6 to 8 years. It was also identified that in boys predominate the combined type and the hyperactive one, while the inattentive type is more prevalent in girls.